-3(3x-5)-3(4x+4)=

Simple and best practice solution for -3(3x-5)-3(4x+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(3x-5)-3(4x+4)= equation:


Simplifying
-3(3x + -5) + -3(4x + 4) = 0

Reorder the terms:
-3(-5 + 3x) + -3(4x + 4) = 0
(-5 * -3 + 3x * -3) + -3(4x + 4) = 0
(15 + -9x) + -3(4x + 4) = 0

Reorder the terms:
15 + -9x + -3(4 + 4x) = 0
15 + -9x + (4 * -3 + 4x * -3) = 0
15 + -9x + (-12 + -12x) = 0

Reorder the terms:
15 + -12 + -9x + -12x = 0

Combine like terms: 15 + -12 = 3
3 + -9x + -12x = 0

Combine like terms: -9x + -12x = -21x
3 + -21x = 0

Solving
3 + -21x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -21x = 0 + -3

Combine like terms: 3 + -3 = 0
0 + -21x = 0 + -3
-21x = 0 + -3

Combine like terms: 0 + -3 = -3
-21x = -3

Divide each side by '-21'.
x = 0.1428571429

Simplifying
x = 0.1428571429

See similar equations:

| 90+2x-16=180 | | 3(5x-2)-3(x+4)= | | 12-(-7)-8= | | -0.2x-0.6=1.2x-0.83 | | 2.3=4.1+y | | -.2k=-15 | | -12n+15=-15-10n | | 2(7-y)=2y+11 | | 2x+15=x+5 | | 24overh=6 | | -13r+10=-4r+19-8r | | (5x-2)+2(x-1)= | | 57=w/3 | | 4(w-2)-w=46 | | sqrtx^4+18x^3+6=3 | | 4x/4=-13/4 | | -(2x-4)-4(x+5)= | | 7x-4=4(x-3) | | 0x=-13 | | 4y+xy+6x+(x*x)+8=z | | 28x+9=9x+41 | | -2(5x+4)-5(4x-3)= | | 10+10k=4k-10-10 | | 100/365 | | -5(2x+3)-(2x+1)= | | (10s^5)(7st^4)= | | 7-(3+5)= | | -1+7u=-10+10u | | -2(4x-3)+5(2x-1)= | | y/-8=10 | | 7(x+8)-32= | | -4v+8=5v-10 |

Equations solver categories